2018
DOI: 10.1186/s13046-018-0934-9
|View full text |Cite|
|
Sign up to set email alerts
|

Abnormally elevated USP37 expression in breast cancer stem cells regulates stemness, epithelial-mesenchymal transition and cisplatin sensitivity

Abstract: BackgroundRecent studies have indicated that deubiquitinating enzymes (DUBs) are related to the stem-cell pathway network and chemo-resistance in cancer. Ubiquitin-specific peptidase 37 (USP37), a novel DUB, was identified to be a potential factor associated with tumor progression. However, the biological functions of USP37 in breast cancer remain unclear.MethodsThe distribution of USP37 expression in breast cancer and the correlation between USP37 expression and the overall survival rate were detected by The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
61
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 55 publications
7
61
0
Order By: Relevance
“…Consistent with the idea that the USP37-depleted cells are undergoing replication stress these cells showed enhanced induction of γH2AX and 53BP1 foci after treatment with aphidicolin along with loss of proliferative capacity upon exposure to multiple forms of replication stress. These results are consistent with a recent study that found USP37-depleted cells are more sensitive to camptothecin (Qin et al, 2018). USP37 has been implicated in the regulation of DNA repair, primarily homologous recombination (HR) (Typas et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with the idea that the USP37-depleted cells are undergoing replication stress these cells showed enhanced induction of γH2AX and 53BP1 foci after treatment with aphidicolin along with loss of proliferative capacity upon exposure to multiple forms of replication stress. These results are consistent with a recent study that found USP37-depleted cells are more sensitive to camptothecin (Qin et al, 2018). USP37 has been implicated in the regulation of DNA repair, primarily homologous recombination (HR) (Typas et al, 2015).…”
Section: Discussionsupporting
confidence: 92%
“…Song et al reported that deubiquitylating enzyme Rpn11 can enhance the chemosensitivity of bortezomib in multiple myeloma cells [35]. Other than that, Qin et al demonstrated that silencing of USP37 can reduce resistance to cisplatin-targeting therapies in breast cancer [36]. In this regard, we also observed that USP32 downregulation could decrease the cisplatinresistance in GC cells, suggesting the involvement of USP32 in drug resistance.…”
Section: Discussionsupporting
confidence: 66%
“…Recent data have reported that the expression of USP37 is elevated in various types of cancers, including breast and lung cancers, and is strongly correlated with the increased mortality rate and metastasis (Pan et al, 2015;Qin et al, 2018). USP37 is found to participate in many biologic processes such as cell growth, mitosis, DNA replication, migration, and EMT, as well as stemness and chemoresistance.…”
Section: Discussionmentioning
confidence: 99%
“…As such, a number of substrates have been identified for USP37 to commensurate its biological functions. For example, USP37 can interact with Hedgehog pathway components Smo and Gli-1 to stabilize these proteins and is essential for stemness maintenance, cell invasion, and EMT in breast cancer (Qin et al, 2018). In lung cancer cells, USP37 promotes cell proliferation and enhances the Warburg effect by directly interacting with c-Myc to deubiquitinate c-Myc (Pan et al, 2015).…”
Section: Discussionmentioning
confidence: 99%